Correlations for evaporation heat transfer coefficient and two-phase friction factor for R-134a flowing through horizontal corrugated tubes - Laohalertdecha, Suriyan; Dalkilic, Ahmet Selim; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Correlations for the evaporation heat transfer coefficient and two-phase friction factor of R-134a flowing through horizontal corrugated tubes are proposed. In the present study, the test section is a horizontal counter-flow concentric tube-in-tube heat exchanger with R-134a flowing in the inner tube and hot water flowing in the annulus. Smooth tube and corrugated tubes with inner diameters of 8.7 mm and lengths of 2000 mm are used as the inner tube. The corrugation pitches are 5.08, 6.35, and 8.46 mm and the corrugation depths are 1, 1.25, and 1.5 mm, respectively. The outer tube is made from smooth copper tube with an inner diameter of 21.2 mm. The correlations presented are formed by using approximately 200 data points for five different corrugated tube geometries and are then proposed in terms of Nusselt number, equivalent Reynolds number, Prandtl number, corrugation pitch and depth, and inside diameter. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Two-phase friction factor; Heat transfer; Temperature; R-134a; Corrugated tube; TWISTED TAPE INSERTS; TURBULENT-FLOW; PRESSURE-DROP; CONDENSATION; ENHANCEMENT; COMBINATION; PREDICTION; ANNULUS; COIL; Thermodynamics; Mechanics